2019
DOI: 10.20546/ijcmas.2019.801.208
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Purification of Recombinant Immunogenic Proteins of Goat Poxvirus in Prokaryotic System

Abstract: Capripox viruses of small ruminants, namely goatpox virus (GTPV) and sheep pox virus (SPPV) are responsible for important contagious diseases that are enzootic to the Indian sub-continent, Africa and the Middle East. In the present study, recombinant F13L and P32 proteins of GTPV were expressed in prokaryotic system, purified and confirmed in Western blot in order to evaluate their diagnostic potential. Full length F13L ( 1 M-L 370 aa) and truncated P32 ( 20 V-S 270 aa) genes of GTPV-Uttarkashi strain were clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…As employed in this study, the P32 has successfully been used for explicit detection and differentiation of goat pox virus [ 10 , 27 – 29 ]. The P32 gene obtained from the samples showed similar resemblance to reference Capripox strains and other goat pox strains [ 12 , 14 , 26 , 30 , 31 ]. Likewise, the nucleotide analysis also yielded a similarity score to other goatpox virus strains [ 10 , 27 ].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…As employed in this study, the P32 has successfully been used for explicit detection and differentiation of goat pox virus [ 10 , 27 – 29 ]. The P32 gene obtained from the samples showed similar resemblance to reference Capripox strains and other goat pox strains [ 12 , 14 , 26 , 30 , 31 ]. Likewise, the nucleotide analysis also yielded a similarity score to other goatpox virus strains [ 10 , 27 ].…”
Section: Discussionmentioning
confidence: 65%
“…Furthermore, a high specificity and sensitivity by PCR confirmation of P32 recombinant plasmid cloned into Pichia host GSII5 compared to serum neutralization test or indirect ELISA has been recorded [ 30 ]. Cloning of F33L and truncated P32 genes by Kumar et al [ 31 ] reported that the purified recombinant was potentially useful for serodiagnosis of capripoxviruses. Utilization of A32L gene from field isolated goat pox virus strain in Taiwan [ 12 ] suggested that multiplex PCR and high resolution melt analysis (HRMA) could play and important role in goat pox virus diagnosis.…”
Section: Discussionmentioning
confidence: 99%